The Effect of Enso and IOD Climate Variability on Salt Production In Nusa Tenggara Islands - Rikha Bramawanto; Fajar Yudi Prabawa; Ifan Ridlo Suhelmi (Jurnal Segara, 2022)
The Nusa Tenggara Islands have an ideal environment for salt production, such as low rainfall and humidity, high evaporation and wind speed, and relatively good seawater quality. However, global climate variability, such as ENSO and IOD, affects the salt harvest volume of the region. This paper aims to discuss the effect of ENSO and IOD climate variability on salt production in the Nusa Tenggara Islands and their comparison with salt production on the islands of Java and Madura. The result shows that salt production in Nusa Tenggara Islands increased when El Nino and positive DMI simultaneously occurred, as in 2012, 2014, and 2015. Conversely, salt production decreased when La Nina and negative DMI simultaneously occurred, as in 2016. When ENSO and DMI are in normal or opposite conditions, salt production is moderate, as in 2013 and 2017. The La Niña event and IOD negative in 2016 triggered high rainfall and salt production decrease in Nusa Tenggara, about 5.8% of the annual average salt production. Meanwhile, this condition also affected salt crop failure on the islands of Java and Madura. Thus, the effect of ENSO and IOD climate variability on salt production in Nusa Tenggara is less significant than in Java and Madura.